A Study on the Spontaneous Combustion Oxidation Properties of Unloaded Coal at Various Surrounding Rock Temperatures. Issue 9 (4th July 2021) - Pan, Rongkun; Tang, Wentao; Wu, Shuaidong; Ma, Junwei; Fu, Dong; Jia, Hailin
ABSTRACT: Based on effects of the deep surrounding rock temperature (Tsr ) on the oxidation properties of mined coal, a thermodynamic experimental system for loaded coal oxidation is employed to examine the oxidation properties of readily oxidizable raw coal samples at various Tsr s and comparatively analyze the patterns of change in the oxygen (O2 ) consumption rate and the carbon monoxide (CO) concentration (CCO ) with Tsr . The infrared (IR) spectra of unloaded coal samples oxidized at various Tsr s were separately fitted to Gaussian curves and Lorentzian curves by using the IR analysis software OMNIC. The following experimental results indicate that Tsr significantly affects the oxidation properties of the coal. The initial Tsr is higher and the rate of increase in the coal temperature is faster during the early stage of oxidation, and the coal–O2 complex effect is higher and the rate of consumption of O2 by coal is higher. The CCO produced by each coal sample continuously increased as Tsr increased. The amount of CO that was produced slowly and linearly increased as Tsr increased during the early stage of oxidation, and it approximately exponentially increases as Tsr increased during the later stage of oxidation. Additionally, the amount of CCO produced is increased with the increase in initial Tsr during the coal oxidation process. By using Fourier-transform IR (FTIR) spectroscopy, microstructural analysis of oxidized coal samples reveals that the characteristics of dynamic change in the micro-active groups (e.g. hydroxyl groups, O-containing functional groups and aromatic and aliphatic hydrocarbons) of unloaded coal samples at various Tsr s, and it also reasonably determines the micro-mechanism of the oxidation properties of unloaded coal samples at various Tsr s.